2020
DOI: 10.3389/fpsyg.2020.00900
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Motives, Laterality, Sports Participation and Competition in Gymnasts

Abstract: The implicit motivational needs for power, achievement, and affiliation are relevant for sports performance. Due to their hypothesized association with functions of the right hemisphere (McClelland, 1986), they may influence lateralized perceptual and motor processes. And due to their interactions with motive-specific incentives, they may influence performance conditional on the presence of suitable incentives. This preregistered study, conducted mostly online, examines motivational needs using a standard pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…Motives were not systematically associated with laterality measures in a way that suggested RH primacy. Although nPower tended to be associated with the CFT in a manner suggesting more RH involvement in men, this was not the case for women, and the pattern was not observed in Schütz and Schultheiss's (2020) earlier study. Perhaps by chance, higher average motives were even associated with an overall more rightward preference and thus LH involvement in terms of hand, foot, ear, and eye use.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Motives were not systematically associated with laterality measures in a way that suggested RH primacy. Although nPower tended to be associated with the CFT in a manner suggesting more RH involvement in men, this was not the case for women, and the pattern was not observed in Schütz and Schultheiss's (2020) earlier study. Perhaps by chance, higher average motives were even associated with an overall more rightward preference and thus LH involvement in terms of hand, foot, ear, and eye use.…”
Section: Discussioncontrasting
confidence: 65%
“…McClelland's claim also fits the observation that the RH is particularly involved in autonomic arousal processes characteristic of emotion and motivation and encompassing cardiovascular, endocrine, and other physiological outputs (Dimond & Farrington, 1977;Wittling, 1995). The only test of his RH hypothesis that we are aware of is a recent study by Schütz and Schultheiss (2020) involving 67 gymnasts. The authors observed correlation patterns of nAchievement and nAffiliation, but not nPower, with a measure of perceptual laterality -the chimeric faces task -that were consistent with the RH hypothesis.…”
Section: Mcclelland's (1986) Right-hemisphere Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the last century, the investigation of human motivation was of central focus in personality research (e.g., McClelland, 1951;Spence, 1958;Schüler et al, 2008;Müller and Cañal-Bruland, 2020;Schütz and Schultheiss, 2020). The motive disposition theory (MDT; e.g., McClelland, 1987) can be described as interactionist: It assumes that motives are dispositions "to respond to specific classes of target states with typical affect patterns" (Langens et al, 2005, p. 73).…”
Section: Psychological Motives and The Grid Techniquementioning
confidence: 99%